Education Quality and Technological Progress in the Business Sector at Different Stages of Economic Development - Majewska, Maria; Mazur-Wierzbicka, Ewa; Duarte, Nelson (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2025)
Objective: To empirically investigate the relationship between education quality and technological progress in the business sector at different stages of economic development. Research Design & Methods: We divided 160 countries into four groups by GDP per capita. The research period was 2007–2021. We use Spearman’s correlation analysis to verify associations between nine indicators for education quality and ten indicators for technological progress. Findings: Our outcomes show that if education quality does not improve, countries do not move up the economic development ladder. Adult literacy, primary education quality, adult skills, and women’s average years in school have the strongest influence on technological progress. Implications / Recommendations: Our paper contains many implications for those seeking to improve social well-being. For example, governments should ensure that women have access to education on equal terms with men. Otherwise, they lose an important source of technological progress and impede the development of human capital. Greater emphasis should be placed on learning how to write and describe reality, read with comprehension, perform simple calculations without a calculator, and teach various learning methods. In the absence of these, the skills of primary, secondary and higher education graduates will not improve. Contribution: The outcomes of our research, both theoretical and empirical, create a multi-faceted approach to the issue of the mutual influence of education and technological progress. They allow us to look at this problem from the perspective of subsequent stages of economic development.